Tratamento do Carcinoma da Próstata Metastizado: Surgimento de Novos Horizontes Terapêuticos - Mota, P (2016)
The evolution in the treatment of metastatic prostate cancer currently provides to the urologist a wide range of therapeutic possibilities that have shown an improvement on overall survival and quality of life of patients. It is presented a clinical case in this article which reflects not only the effectiveness of these therapies but also their rapid evolution.